Role of Potential COVID-19 Immune System Associated Genes and the Potential Pathways Linkage with Type-2 Diabetes - Helmi, Nawal; Alammari, Dalia; Mobashir, Mohammad (Combinatorial Chemistry & High Throughput Screening, 2022)
Background: Coronavirus is an enclosed positive-sense RNA virus with club-like spikes extending from its surface. It is most typically associated with acute respiratory infections in humans, but its capacity to infect many host species and cause multiple illnesses makes it a complicated pathogen. The frequent encounters between wild animals and humans are a typical cause of infection. The zoonotic infections SARS-CoV and MERS-CoV are among the most common causes of serious respiratory illnesses in humans. Aim: The main goal of this research was to look at gene expression profiles in human samples that were either infected with coronavirus or were not, and compare the varied expression patterns and their functional implications. Methods: The previously researched samples were acquired from a public database for this purpose, and the study was conducted, which included gene expression analysis, pathway analysis, and network-level comprehension. The results for differentially expressed genes, enriched pathways, and networks for prospective genes and gene sets are presented in the analysis. In terms of COVID-19 gene expression and its relationship to type 2 diabetes. Results: We see a lot of genes that have different gene expression patterns than normal for coronavirus infection, but in terms of pathways, it appears that there are only a few sets of functions that are affected by altered gene expression, and they are related to infection, inflammation, and the immune system. Conclusion: Based on our study, we conclude that the potential genes which are affected due to infection are NFKBIA, MYC, FOXO3, BIRC3, ICAM1, IL8, CXCL1/2/5, GADD45A, RELB, SGK1, AREG, BBC3, DDIT3/4, EGR1, MTHFD2, and SESN2 and the functional changes are mainly associated with these pathways: TNF, cytokine, NF-kB, TLR, TCR, BCR, Foxo, and TGF signaling pathways are among them and there are additional pathways such as hippo signaling, apoptosis, estrogen signaling, regulating pluropotency of stem cells, ErbB, Wnt, p53, cAMP, MAPK, PI3K-AKT, oxidative phosphorylation, protein processing in endoplasmic reticulum, prolactin signaling, adipocytokine, neurotrophine signaling, and longevity regulating pathways. SMARCD3, PARL, GLIPR1, STAT2, PMAIP1, GP1BA, and TOX genes and PI3K-Akt, focal adhesion, Foxo, phagosome, adrenergic, osteoclast differentiation, platelet activation, insulin, cytokine- cytokine interaction, apoptosis, ECM, JAK-STAT, and oxytocin signaling appear as the linkage between COVID-19 and Type-2 diabetes.
Keywords: gene expression profiling